Sublimating Contentious Chinese Politics into Local Public Administration: A Polity-Centered Analysis of Authoritarian Governance and Administrative Responsibility. (14th November 2017) - Lei, Shaohua; Green, Richard
Abstract : An important aspect of Chinese governance today involves the sublimation of contentious politics into local administration through a complex multilevel system of administrative responsibility. Chinese governance remains largely opaque to outsiders, and even insiders may not fully grasp all its nuances. With that caveat in mind, this article provides some insight on how the Chinese national government and party leaders cope with increasingly contentious politics and administration at local levels. The dynamics described here play an important role in the Communist Party's efforts to sustain its legitimacy while pursuing rapid economic transformation. The analysis is informed by a "polity, " or regime-centered, model that emphasizes the interplay of contextual settings, core political values, authority structures and processes, coping strategies, and cultivation of organizational leadership and management competencies. The findings, drawn from 445 interviews conducted over eight years (2003–2015) and across 16 provinces, 84 cities, and 1, 092 incidents of local mass conflict, illustrate how responsibility and performance are defined through multilevel tactics in a process of political and administrative jockeying among contending stakeholders in which local governments buffer the effects of angry local protests, and support the legitimacy of the party and the national government.